Look East, Cross Black Waters India's Interest in Southeast Asia - Blank, Jonah (RAND Corporation, 2015)
India's core goals for Southeast Asia are in basic harmony with those of the United States, including regional stability, peaceful settlement of territorial disputes, and containment of radicalism Still, America should not expect India to enter any sort of alliance, nor join any coalition to balance against China, but should demonstrate strategic patience and willingness to cultivate a long-term relationship.